Implementation of Geometric Quantum Gates on Microwave‐Driven Semiconductor Charge Qubits. Issue 8 (12th June 2021) - Zhang, Chengxian; Chen, Tao; Wang, Xin; Xue, Zheng‐Yuan
Abstract: A semiconductor‐based charge qubit, confined in double quantum dots, can be a platform to implement quantum computing. However, it suffers severely from charge noises. Here, a theoretical framework to implement universal geometric quantum gates in this system is provided. It is found that, while the detuning noise can be suppressed by operating near its corresponding sweet spot, the tunneling noise, on the other hand, is amplified and becomes the dominant source of error for single‐qubit gates, a fact previously insufficiently appreciated. It is demonstrated, through numerical simulation, that the geometric gates outperform the dynamical gates across a wide range of tunneling noise levels, making them particularly suitable to be implemented in conjunction with microwave driving. To obtain a nontrivial two‐qubit gate, a hybrid system is introduced with charge qubits coupled by a superconducting resonator. When each charge qubit is in resonance with the resonator, it is possible to construct an entangling geometric gate with fidelity higher than that of the dynamical gate for experimentally relevant noise levels. Therefore, the results suggest that geometric quantum gates are powerful tools to achieve high‐fidelity manipulation for the charge qubit. Abstract : Geometric gates, which make use of the geometric phase—a global property, are powerful tools to combat noises. This paper demonstrates that geometric gates can outperform dynamical gates across a wide range of noise levels in semiconductor quantum dots, making them particularly suitable to be implemented in controlling semiconductor charge qubits.